Water and oil flow regime identification using transmission-mode ultrasonic tomography - Muhamad Ahnaf, Mohd Abd. Ghafar (2012)
The purpose of this project is to develop a suitable ultrasonic tomography system that can identify two phase flow regime. By using ultrasonic, emphasis is placed on the evaluation of its performance in flow regime identification and cross-sectional measurement. The transmission-mode approach has been used for sensing the water and oil two-phase flow. The transmission mode for sensing purpose was implemented where 4x4 projections is produced. This is one of the non-invasive methods that do not disturb the internal flow of the pipeline, hence, water and oil flow inside the pipe could be monitored by this system in an uninterrupted manner and flow regime determined based on the sum of all the sensor’s values. Analysis and result measurement was using oscilloscope are presented.